الحماية الإشعاعية للأشعة المؤينة وفوق البنفسجية من ناضح هيموغلوبين كريات الدم الحمراء - الجبوري, حسين علي; سيه, بيداء طاهر (Al-Nahrain Journal of Science, 2018)
Superannuate isolated from heamolysid human erythrocytes, gives gamma–radiation dose of 200 Krad, provide an outstanding protection against the damaging effects of ultraviolet and gamma-radiation. The radiation protection-P% in RBC samples with irradiated Diluted superannuated was 66% while in un irradiated diluted superannuated was 10%. The protein which extracted from irradiated diluted superannuated produce radiation protection- P%: 84% against the effect of ultraviolet radiation and 72% for protein which extracted from un irradiated diluted superannuated. Take into account the ionic efflux for potassium-K ,calcium–Ca, magnesium-Mg and the modified protein have been tested and the hater could be a key factor to this outstanding phenomenon, This study showed the effect of radiation protection was related to SH-qroup in hemoglobin structure and formation of the preservative components of S–sulphur which interaction with free radicals analysis. The results of this study don't decided the meager reason of the process of radiation protection but refer to the important of the formation increases of glutathione and sulfmoglobine for protection with ionic efflux.